Data Serialization Formats for the Internet of Things - Friesel, Daniel; Spinczyk, Olaf (Electronic Communications of the EASST, 2021)
IoT devices rely on data exchange with gateways and cloud servers. However, the performance of today’s serialization formats and libraries on embedded systems with energy and memory constraints is not well-documented and hard to predict. We evaluate (de)serialization and transmission cost of mqtt.eclipse.org payloads on 8- to 32-bit microcontrollers and find that Protocol Buffers (as implemented by NanoPB) and the XDR format, dating back to 1987, are most efficient.